Evaluation of the cytotoxic effect of antimicrobial photodynamic therapy on fibroblasts (NIH/3T3) and expression of Bcl-2 family genes - Lamarque, Giuliana de Campos Chaves (2019)
Antimicrobial photodynamic therapy (aPDT) has been used as an adjuvant treatment of oral infections in a minimal intervention clinical approach. Its antimicrobial efficacy was demonstrated in several studies; however, there is a lack of evidence on its cytotoxic effects on eukaryotic cells. The aim of this study was to evaluate the cytotoxicity of aPDT mediated by two photosensitizing agents, methylene blue and curcumin, on mouse fibroblasts. Cells were treated with 0.1 or 1.0 mg.mL-1 methylene blue (MB) associated or not to LED at 630 nm, or 0.6 or 6 M curcumin combined or not with LED at 455 nm, with densities of 0.075 or 7.5 J.cm-2. Cellular viability was examined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and crystal violet (CV) assays. The expression of cDNA for Bax, Bad, Bcl-2, VDAC-1, cytochrome C and Fas-L genes related to apoptosis was assessed by quantitative PCR (qPCR) after 1, 3, 6 and 24 h from treatments. The differences between groups were detected by Kruskal-Wallis and post-hoc Dunn\'s tests for MTT and CV assays, and by ANOVA and post-hoc Tukey test for qPCR (P<0.05). The combination of 1.0 mg.mL-1 MB and 7.5 J.cm-² LED significantly reduced the cellular viability. The same was observed for the combinations of 6 M curcumin plus 0.075 and 7.5 J.cm-2 LED, which reduced viable cells in 47% and 99%, respectively. Also, the combination of 0.6 M curcumin plus 7.5 J.cm-2 LED reduced the viability of fibroblasts in 34%. MB-mediated aPDT increased the expression of cytochrome C and Fas-L after 3 h, and Bax/Bcl-2, Bad/Bcl-2, and VDAC-1 after 6 h from treatments. Curcumin-mediated aPDT increased significantly the relative expression of Bax/Bcl-2, cytochrome C, VDAC-1, and Fas-L genes. Therefore, MB- and curcumin-mediated aPDT induced cytotoxicity on mouse fibroblasts, with consequent activation of Bcl-2 apoptosis signaling pathways. Further studies are needed to determine the adequate parameters of aPDT to inactivate microorganisms without damaging eukaryotic cells.